Entrepreneurial Challenges and Issues: A Case Study of Undergraduate Entrepreneurs in Malaysia - Wei Chien Ng; Paul Dung Gadi; Zhao Shengnan; Rong Sidan; Song Ruixuan; Mohammad Shukor Bin Md Zain; Mohd Fazmin Syazwan Bin Muhammad Fauzie; Daisy Mui Hung Kee; Anees Janee Ali (Journal of The Community Development in Asia, 2025)
This study aims to examine the key challenges encountered by Malaysian university students in their entrepreneurial journey, identify the underlying causes, and propose practical recommendations for improvement. Employing a quantitative research design, the study surveyed 100 undergraduate students from Universiti Sains Malaysia (USM) through Google Forms. The findings reveal that entrepreneurial barriers predominantly arise from five major factors: aversion to stressed hard work, aversion to risk, fear of failure, lack of social networking, and lack of resources. These challenges reflect both individual limitations and structural constraints that hinder students’ entrepreneurial engagement and sustainability. Based on the analysis, the study suggests several measures to strengthen entrepreneurial ecosystems in higher education, including enhancing institutional support, optimizing access to funding, improving government policies and regulatory frameworks, and fostering an entrepreneurial culture on campus. Overall, this research contributes to a deeper understanding of the entrepreneurial difficulties faced by university students in Malaysia and highlights the need for integrated efforts from universities, policymakers, and industry stakeholders to cultivate a more supportive environment for student entrepreneurship.